Communicative ❤ Intimacies: Influencers and Perceived Interconnectedness - Abidin, Crystal (2015)
Around the world, many young people have taken to social media to monetise their personal lives as “influencers.” Although international news reports have variously described these commercial social media users as “bloggers,” “YouTubers,” and “Instagrammers,” I conceptualise these high-profile Internet microcelebrities (Senft 2008) as influencers regardless of their digital platform. Influencers are everyday, ordinary Internet users who accumulate a relatively large following on blogs and social media through the textual and visual narration of their personal lives and lifestyles, engage with their following in digital and physical spaces, and monetise their following by integrating “advertorials” into their blog or social media posts. A pastiche of “advertisement” and “editorial”, advertorials in the Influencer industry are highly personalised, opinion-laden promotions of products/services that influencers personally experience and endorse for a fee.